2004
DOI: 10.1063/1.1707232
|View full text |Cite
|
Sign up to set email alerts
|

Core-level photoemission and near-edge x-ray absorption fine-structure studies of GaN surface under low-energy ion bombardment

Abstract: We have investigated compositional changes on GaN surfaces under low-energy Ar ion bombardment using synchrotron-based high-resolution core-level photoemission measurements and near-edge x-ray absorption fine-structure ͑NEXAFS͒ spectroscopy. The low-energy ion bombardment of GaN produces a Ga-rich surface layer which transforms into a metallic Ga layer at higher bombarding energies. At the same time, the photoemission spectra around the N 1s core level reveal the presence of both uncoordinated nitrogen and nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 34 publications
5
15
0
Order By: Relevance
“…35 This assignment is in agreement with combined x-ray photoemission and NEXAFS characterization of Ar + bombarded GaN. 36 A similar RL has been observed in the N K edge NEXAFS spectra of N-rich Si x N y ͑Refs. 37-39͒ and Si x N y O z ͑Ref.…”
Section: B Nexafs Resultssupporting
confidence: 72%
“…35 This assignment is in agreement with combined x-ray photoemission and NEXAFS characterization of Ar + bombarded GaN. 36 A similar RL has been observed in the N K edge NEXAFS spectra of N-rich Si x N y ͑Refs. 37-39͒ and Si x N y O z ͑Ref.…”
Section: B Nexafs Resultssupporting
confidence: 72%
“…19 Excitations of core-electrons to an unoccupied defect level may produce an additional peak in NEX-AFS spectra, related directly to the presence of that specific defect in the material. 20,21 In the present study we focus on NEXAFS measurements around K-edges of boron and nitrogen in BN. For electronic transitions around the K-edge, where the initial state is a 1s state, the final states must contain contributions from p orbitals, for example in the form of s + p z ͑referred to as ‫ء‬ transitions͒ or p x + p y ͑ ‫ء‬ transitions͒ due to the dipole selection rule ⌬l= Ϯ 1, where ⌬l is the change of the angular momentum quantum number between the initial and final states.…”
Section: Resultsmentioning
confidence: 99%
“…5, for the untreated GaN surface, the Ga 3d spectrum can be decomposed into three components in addition to the Ga-N component (19.6 eV): those chemically shifted by 0.92 eV toward higher binding energy (BE), 0.49 toward lower BE, and 1.76 eV toward lower BE, which can be assigned to Ga bonding to oxygen (Ga-O; 20.5 eV) [21,22], Ga bonding to N-H (Ga-NH; 19.21 eV) [23], and metallic Ga (17.5-18.4 eV) [24]. It has been reported that a metallic Ga layer forms on a damaged GaN surface [25]. Such a metallic Ga layer is readily oxidized even in air to afford Ga oxide on an untreated GaN surface.…”
Section: Chemical Propertiesmentioning
confidence: 96%